Políticas para educação e suas implicações no trabalho, profissão e profissionalização docente em unidades acadêmicas da Universidade Federal de Goiás (UFG) - Paz, Suelaynne Lima da (2016)
This research is part of the State, Policies and History of Education of the Graduate Program in Education at the Federal University of Goiás and aims to raise, analyse and understand the foundations of the profession and professionalisation lecturer at UFG and its relations with the public policies of higher education from 1990, specifically the expansion and regulatory policies of teaching in university teaching. Therefore, it was conducted literature searches in national and journals indexed by CAPES as Qualis A and GT11 of Anped in the period 2005-2014 and consultations on the portal of dissertations and theses of Capes. Also the Universitas / Br Network productions were analyzed and made the collection and analysis of national documents on public policies for higher education and institutional documents of UFG. In empirical research, favored up interviews with managers and academic researchers stricto sensu graduate programs at UFG, belonging to three academic units, representative of Exact Sciences knowledge areas and Earth, Life Sciences and umanities. The current context of change for the flexible accumulation regime, the search for new niches of accumulation of capital and the State reform comes in the context of the nfolding public University in its overlap with the productive sector, through a reform carried out over the past decades. The impacts of this reform have raised flexibilisation and intensification processes ofteaching work that impact on the profession and on teacher rofessionalization of this level of education. The main policies that give sustainability to these processes in he federal universities relate to the expansion policy promoted by Reuni and the regulation of academic and scientific production conducted by Capes. These policies are analyzed in the context of the UFG and are impregnated in the daily teaching work, fact giving new contours for the teaching profession in university teaching, with the weakening of the subjective conditions of work and struggles in relation to career development, and causing some union breakdown. However, research shows that, although there are aspects that influence the teaching work to be more aligned with the requirements of productive field and make the foundations of the profession and professionalisation fragile, there is some maintenance, on teaching academic culture, traces of a sociability that integrates the collective as fundamental. Such process is possible especially for the intangible nature of teaching, which enables symbolic exchanges between teachers, strengthening the construction of teaching as a collectivity.